2018
DOI: 10.4103/jpbs.jpbs_217_17
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia in advanced HIV infection with hyperinfection syndrome: A case report

Abstract: Strongyloides stercoralis is a soil-transmitted helminth that occurs almost worldwide, yet estimates about its prevalence are not well documented. The spectrum of clinical manifestations of strongyloidiasis is wide, ranging from asymptomatic disease to hyperinfection or dissemination of larvae involving multiple organ systems. Immunosuppression can increase the risk of hyperinfection syndrome in patients with strongyloidiasis. Strongyloidiasis continues to remain a neglected tropical disease, the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Few previous reports from India have shown that the prevalence of S. stercoralis in HIV-infected patients ranged from 0% to 27.3% [ 3 ]. However, cases of SHS have been rarely described in HIV-infected patients in India [ 4 , 5 ]. The absence is explained by the fact that in HIV-positive patients with higher CD4 + cell counts, direct development of infective filariform larvae in the gut (autoinfection) is favored, compared with those with lesser immune function (low CD4 count or advanced HIV disease), in whom, indirect development is favored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few previous reports from India have shown that the prevalence of S. stercoralis in HIV-infected patients ranged from 0% to 27.3% [ 3 ]. However, cases of SHS have been rarely described in HIV-infected patients in India [ 4 , 5 ]. The absence is explained by the fact that in HIV-positive patients with higher CD4 + cell counts, direct development of infective filariform larvae in the gut (autoinfection) is favored, compared with those with lesser immune function (low CD4 count or advanced HIV disease), in whom, indirect development is favored.…”
Section: Discussionmentioning
confidence: 99%
“…S. stercoralis remains a neglected tropical disease, and its association with HIV coinfection is sparsely studied in resource-limited settings such as India. It is reflected by the paucity of the published literature on HIV/ S. stercoralis coinfection [ 3 5 ]. Since 2005, there have been reports of seven patients presenting with SHS after antiretroviral therapy (ART) initiation [ 6 12 ].…”
Section: Introductionmentioning
confidence: 99%